Immunogenicity and safety of the third booster dose of the inactivated Japanese encephalitis vaccine in Korean children: A prospective multicenter study. Issue 14 (1st April 2021) - Kwak, Byung Ok; Kwon, Young Se; Hong, Young Jin; Shin, Seon Hee; Eun, Byung Wook; Ahn, Young Min; Kim, Hwang Min; Kim, Nam Hee; Kim, Dong Hyun
Abstract: The immunization schedule for the inactivated Japanese encephalitis (JE) vaccine in Korea is a two-dose primary series at 12–24 months of age and three booster doses at 12 months after primary schedule and at 6 and 12 years of age. The aim of this study was to investigate immunogenicity and safety of the third booster dose of the inactivated JE vaccine, as well as the long-term immunogenicity of the second booster dose in Korean children. Healthy children aged 11–13 years, primed and given four doses of inactivated JE vaccines were included. All subjects received the third booster dose of the JE vaccine. Neutralizing antibody (NTAb) titers were assessed before and 4–6 weeks after vaccination using plaque reduction neutralization test (PRNT), and were considered to be protective at ≥ 1:10. Local and systemic adverse events were monitored for 4 weeks after vaccination. Before and after booster vaccination, all seroprotection rates were 100%. Geometric mean titer (GMT) showed a 6.05–fold increase, from 139.11 (95% CI: 110.76, 174.71) to 841.53 (95% CI, 714.25, 991.50). The local tolerability and systemic safety profiles were favorable, with no serious adverse events. In conclusion, the third booster dose of the inactivated JE vaccine was demonstrated to be safe and immunogenic in Korean children when administered according to the current immunization schedule.